Bioaccumulation of heavy metals in downstream ecosystem of Sembilang River, Kuala Selangor, Malaysia - Nik Adnan, Nik Nur Izzattun; Che Nor Din, Nur Rifqah Safira; Muhamad Rasid, Nur Anisa (2020)
Accumulation of heavy metals (Copper, Zinc, Lead and Cadmium) were investigated in downstream ecosystem of Sembilang River, Kuala Selangor, Malaysia. The development of various industries and landfill along the Sembilang River have high tendency for being effected towards the quality level of water resources. The distribution of heavy metals in water resource lead to huge impacts towards aquatic organisms such as fish and able to be human health threat. Heavy metal is easily deposited in the sediment and immobilized through adsorption and coagulation. This study aims to access the accumulation of Copper, Zinc, Lead and Cadmium in water, sediment and Sembilang fish (Plotosus canius) from Sembilang River, Kuala Selangor, Malaysia. Further, the potential health risk of heavy metals in Sembilang fish (Plotosus canius) were determined. In the study, samples of water and sediment were collected from five sampling points with the distance of 250m from each sampling points. Meanwhile, the Sembilang fish (Plotosus canius) samples were collected from the river estuary area of Sembilang River. Prior for analysis, the acid digestion procedure were conducted on water and sediment samples and dry ashing procedure for fish samples. All the samples were analyzed for Copper, Zinc, Lead and Cadmium using Atomic Absorption Spectrometer. In general, the heavy metals content in sediment indicate that Zinc as the highest mean values in the study area for all sampling sites followed by Copper and Lead. In term of water quality, the presence of heavy metals concentration along this river could be shows as Lead > Cadmium > Zinc > Copper. The result on fish samples stated that Lead and Zinc concentration were highest in the gills of the fish. Meanwhile, Cadmium and Copper contents were mainly enriched in the muscle of the fish. The results and further health risk assessments revealed that the consumption of Sembilang fish (Plotosus canius) from Sembilang River, Kuala Selangor is free from the probable carcinogenic and non-carcinogenic risks. Overall, this investigation indicate that the concentrations of heavy metals in the sediment and muscle tissue of the studied fish were lower than the limits as set in Sediment Quality guidelines, Food and Agriculture Organization, 1983 and Malaysian Food Regulations, 1985. Lead and Cadmium at certain sampling points for Sembilang River water samples have exceeded the acceptable level of National Water Quality Standards.